Effects of Zinc Compounds on the Enzymatic Activities of Lysozyme and Peroxidase and Their Antifungal Activities - Kim, Yongdae; Chang, Ji-Youn; Kim, Yoon-Young; Lee, Jae Wook; Kho, Hong-Seop (Springer Nature, 2024)
This study aimed to investigate the effects of zinc compounds on the enzymatic activities of lysozyme, peroxidase, and the glucose oxidase-mediated peroxidase (GO-PO) system and their antifungal activities. Four different zinc compounds (zinc chloride, gluconate, lactate, and sulfate) were incubated with hen egg-white lysozyme (HEWL), bovine lactoperoxidase (bLPO), the GO-PO system, and human unstimulated whole saliva in solution and on a hydroxyapatite surface. Enzymatic activities of lysozyme, peroxidase, and the GO-PO system were measured through the hydrolysis of Micrococcus lysodeikticus, oxidation of fluorogenic 2 ',7 '-dichlorofluorescin, and glucose assay, respectively. Interactions between zinc and enzymes were analyzed by surface plasmon resonance (SPR). The minimum inhibitory concentration (MIC) and candidacidal activities of zinc compounds were examined against three Candida albicans strains. Zinc gluconate and sulfate significantly increased the enzymatic activities of salivary lysozyme in the solution assay and of HEWL and salivary lysozyme on the hydroxyapatite surface. However, all examined zinc compounds significantly decreased the enzymatic activities of bLPO and salivary peroxidase in solution and on the surface. SPR analyses revealed binding of zinc to lysozyme and peroxidase, with affinity differing according to the zinc compounds. The MIC of zinc compounds against C. albicans was 1.0-2.4 mM. Candidacidal activities were 17.7-38.8% and 23.7-47.0% at 1.0 and 10 mM concentrations, respectively. In conclusion, zinc compounds enhanced lysozyme activity but inhibited peroxidase activity. Zinc compounds exhibited concentration-dependent candidacidal activity against C. albicans. Zinc compounds are potential therapeutic agents for oral health, especially for geriatric patients.